This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: adams (bda255) HW11 Radin (56635) 1 This printout should have 17 questions. Multiplechoice questions may continue on the next column or page find all choices before answering. 001 10.0 points Compute the value of lim n 3 a n b n 5 a n 2 b n when lim n a n = 6 , lim n b n = 2 . 1. limit = 19 17 2. limit = 18 17 3. limit doesnt exist 4. limit = 19 17 5. limit = 18 17 correct Explanation: By properties of limits lim n 2 3 a n b n = 3 lim n a n lim n b n = 36 while lim n (5 a n 2 b n ) = 5 lim n a n 2 lim n b n = 34 negationslash = 0 . Thus, by properties of limits again, lim n 3 a n b n 5 a n 2 b n = 18 17 . 002 10.0 points Find a formula for the general term a n of the sequence { a n } n =1 = braceleftBig 1 , 2 3 , 4 9 , 8 27 , . . . bracerightBig , assuming that the pattern of the first few terms continues. 1. a n = parenleftBig 3 4 parenrightBig n 2. a n = parenleftBig 2 3 parenrightBig n 3. a n = parenleftBig 2 3 parenrightBig n 1 correct 4. a n = parenleftBig 3 2 parenrightBig n 1 5. a n = parenleftBig 3 4 parenrightBig n 1 6. a n = parenleftBig 3 2 parenrightBig n Explanation: By inspection, consecutive terms a n 1 and a n in the sequence { a n } n =1 = braceleftBig 1 , 2 3 , 4 9 , 8 27 , . . . bracerightBig have the property that a n = ra n 1 = parenleftBig 2 3 parenrightBig a n 1 . Thus a n = ra n 1 = r 2 a n 2 = . . . = r n 1 a 1 = parenleftBig 2 3 parenrightBig n 1 a 1 . Consequently, a n = parenleftBig 2 3 parenrightBig n 1 since a 1 = 1. keywords: sequence, common ratio 003 10.0 points adams (bda255) HW11 Radin (56635) 2 Determine whether the sequence { a n } con verges or diverges when a n = 6 n 2 6 n + 3 n 2 + 4 n + 1 , and if it does, find its limit 1. the sequence diverges 2. limit = 1 2 correct 3. limit = 1 4 4. limit = 0 5. limit = 1 6 Explanation: After bringing the two terms to a common denominator we see that a n = 6 n 3 + 6 n 2 (6 n + 3) ( n 2 + 4 ) (6 n + 3) ( n + 1) = 3 n 2 24 n 12 6 n 2 + 9 n + 3 . Thus a n = 3 24 n 12 n 2 6 + 9 n + 3 n 2 ....
View
Full
Document
This note was uploaded on 04/30/2009 for the course CH 302 taught by Professor Holcombe during the Spring '07 term at University of Texas at Austin.
 Spring '07
 Holcombe

Click to edit the document details